Effect of Clitoria ternatea Tea on Triglyceride levels in High Fat High Fructose Diet Fed Rats - Damar Adi Nugraha; Hesty Wahyuningsih (Jurnal EduHealth, 2026)
High triglyceride levels are one of the criteria for metabolic syndrome, which has a high prevalence. Butterfly pea flowers (Clitoria ternatea L.) contain flavonoids and polyphenols that have the potential to lower triglyceride levels. However, tea preparations have not yet been proven to lower triglycerides. This study aimed to determine the effect of butterfly pea flower tea on triglyceride levels in male Wistar rats (Rattus norvegicus) induced by a high-fat, high-fructose diet. This is an experimental study with a post-test only control group design. The study was conducted at the Center for Food and Nutrition Studies, Gadjah Mada University. For 22 days, 30 male Wistar rats were randomly divided into 5 groups. Group K0 was given standard feed, group K(–) was given a high-fat diet (2 ml/200 gBW/day) and fructose (1 ml/200 gBW/day), group P1 was given a high-fat high-fructose diet and butterfly pea flower extract at a dose of 80 mg/200 gBW, group P2 was given a high-fat high-fructose diet and butterfly pea flower tea at a dose of 36 mg/200 gBW, and group P3 was given a high-fat high-fructose diet and butterfly pea flower tea at a dose of 72 mg/200 gBW. The data obtained were analyzed using the One-Way ANOVA test and continued with the Post Hoc LSD test. The average triglyceride levels showed that the groups were K(-) 136.73 mg/dL, P2 111.23 mg/dL, P3 88.77 mg/dL, P1 85.96 mg/dL, and K0 70.99 mg/dL. One-Way ANOVA test showed significant differences between groups (p<0.05), the results of Post Hoc LSD K(-) and P3 were significantly different. Administration of butterfly pea flower tea (Clitoria ternatea L.) has an effect on triglyceride levels in high fat high fructose diet model mice.